Agreement with SCCI (Institutional Knowledge at Singapore Management University, 2001)
On 13 January 2001 Singapore Management University signed a memorandum of understanding with the Singapore Chinese Chamber of Commerce and Industry. Seated on the left, from left to right, SCCCI Vice President Gan See Khem and SCCCI President Tay Beng Chua. Three members of SCCCI stand behind them. Seated on the right, from left to right, SMU President Janice Bellace and SMU Provost Tan Chin Tiong. Standing on the left are SMU Chairman Ho Kwon Ping, SMU Deputy President Tan Teck Meng and SMU Dean Pang Yang Hoong.